The Effect Of Profitability, Liquidity, Leverage, Company Size and Assets Growth on Stock Return: Empirical evidence from Indonesia - Nahdhiyah, Avivah Inaroh; Alliyah, Siti (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
The consumer goods industry sector has a significant impact and influence on the Indonesian economy. This investigation aimed to determine the impact of profitability, liquidity, leverage, firm size and asset growth on stock returns. This study used purposive sampling to obtain a sample of 18 consumer goods industry registered with IDX in 2017-2021. Methods of data collection using documentation. The data analysis technique uses multiple linear regression. The result of this investigation indicated that profitability has a significant positive effect on stock returns. Company size has a negative significant effect on stock returns, while liquidity, leverage and asset growth positively affect stock returns. In conclusion, profitability affects stock returns, while liquidity, leverage, firm size and asset growth do not affect stock returns. This research contributes to investors' decision-making regarding stock returns in companies in the consumer goods industry. The implication of this research can be helpful for investors and entities to find out the prospects for entities and provide additional knowledge for readers and other researchers.